(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article examines modern approaches to teaching the Russian language, focusing on the use of computer technologies in the educational process. Innovative methods such as interactive programs and applications, online courses, multimedia materials and virtual classrooms provide students with unique opportunities for effective and engaging language learning. Automated task checking, individualized training and gamification of the learning process complement this approach, promoting the formation of Russian language skills, taking into account modern educational requirements. The advantages of this approach are discussed, including flexibility, accessibility and motivation, which makes the process of learning the Russian language more effective and attractive for a variety of categories of students.